The Importance Of The Teacher's Role In The Learning Process - Zulfatunnisa, Shobrina (Jurnal Gentala Pendidikan Dasar, 2022)
This article aims to find out how important the teacher's role is in the learning process. The writing of this article was carried out using the Study Library or SLR (Systematic Literature Review) method. Data collection techniques by looking for various journal references related to the importance of the teacher's role in the learning process. After searching for various references, the author reads, selects, analyzes, and presents systematically in this article. The results of this article present 20 topics of discussion. Based on the results of this activity, the authors can conclude that the teacher plays a very important role in the learning process. The teacher is the executor of the teaching and learning process so that the success of education is very dependent on the quality of the teaching. In teaching and learning activities, one of the important roles of teachers is to make the knowledge taught can be easily accepted by students. Not only play a role in teaching knowledge, teachers also play a lot in the learning process outside of science. Lack of understanding in learning can be caused by several factors. One of them is the lack of sensitivity of a teacher as a teacher in the learning process at school. This causes a decrease in children's understanding, especially elementary school children. Lack of grasping power of something seen and heard by elementary school children, the role of the teacher is needed for students whose understanding of something is relatively low.